Rainbows of intelligence : exploring how students learn - Teele, Sue. (Thousand Oaks, CA : Corwin, 2000)
Foreword by Thomas Armstrong Rainbows of Intelligence explores the range of students' intelligence and learning potential through the metaphor of rainbows and colors. The book includes anbsp;variety of lessons plans.
Includes bibliographical references.
Keywords: Learning, Psychology; Multiple intelligences; Cognitive styles in children